2016
DOI: 10.1016/j.nut.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Soluble arabinoxylan enhances large intestinal microbial health biomarkers in pigs fed a red meat–containing diet

Abstract: 17Objectives 18To investigate how moderately increased dietary red meat combined with a soluble fibre 19 (wheat arabinoxylan-AX) alters the large intestinal microbiota, in terms of fermentative 20 end-products, and microbial community profiles, in pigs. 21 Methods 22Four groups of ten pigs were fed Western-type diets containing two amounts of red meat, 23 with or without a solubilized wheat arabinoxylan-rich fraction for four weeks. Following 24 euthanasia, fermentative end-products (short-chain fatty acids (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Furthermore, in a study with human subjects by Wu et al [ 3 ], the Bacteroides enterotype was highly associated with animal protein, several amino acids, and saturated fats, which suggests that meat consumption according to a Western diet is characteristic for this enterotype. Within this regard, Williams et al [ 66 ] recently investigated the impact of solubilized wheat arabinoxylans (AX) added to red meat diets fed to pigs. A counteracting potential of AX could be observed, characterized by reduced protein fermentation and lower microbial production of toxic end products such as ammonia in cecum and colon, while, e.g., the Bacteroides fragilis group was relatively high in pigs fed the red meat diet devoid of AX.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study with human subjects by Wu et al [ 3 ], the Bacteroides enterotype was highly associated with animal protein, several amino acids, and saturated fats, which suggests that meat consumption according to a Western diet is characteristic for this enterotype. Within this regard, Williams et al [ 66 ] recently investigated the impact of solubilized wheat arabinoxylans (AX) added to red meat diets fed to pigs. A counteracting potential of AX could be observed, characterized by reduced protein fermentation and lower microbial production of toxic end products such as ammonia in cecum and colon, while, e.g., the Bacteroides fragilis group was relatively high in pigs fed the red meat diet devoid of AX.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of arabinose to xylose can be used to describe a characteristic of AX structure. AX accounts for approximately 20% of the content of wheat bran [ 32 ], and, in its purified form has been shown to be readily fermentable both in vitro [ 33 ], and in the caecum of grower pigs [ 34 ]. In addition, it was shown that for different AX-containing rye milling fractions, there were significant differences in fermentability, which were ascribed to variation in alkali-labile crosslinks with lignin, rather than actual AX structure [ 35 ].…”
Section: Plant Cell Walls and Their Components-definition And Physmentioning
confidence: 99%
“…Monitoring fermentation kinetics within the human gut is also difficult, however it is important when the fate of ingested food from digestive physiology to gut microbiology is considered. A wide range of techniques, from batch in vitro (Hummel et al 2006;Rymer et al 2005;Wang et al 2016) to semi-continuous or continuous fermentation models (Tanner et al 2014), inoculated with faeces have been described, that predict the impact of diet on the composition and functionality of the gut microbiota (Williams et al 2016). Both human and animal (e.g.…”
Section: Declaration By Authormentioning
confidence: 99%
“…The fermentation of resistant starch and cell wall components by colonic microbiota is known to produce beneficial metabolites such as short chain fatty acids (SCFA), mainly acetate, propionate, and butyrate (Rose et al 2007). Moreover, fermentable carbohydrates have also been reported to be helpful in cholesterol reduction, colonic microbiota stabilisation, faecal bulking and water retention (Williams et al 2016). The presence of undigested lipids in the ileum has been proposed to enhance satiety through triggering of the ileal brake mechanism in human and animal studies (Brown et al 1993;RI & Read 1984;Spiller et al 1984;Strader & Woods 2005).…”
Section: Grain Milling and Implications For Functionalitymentioning
confidence: 99%
See 1 more Smart Citation